An Empirical Inquiry into Per Capita Convergence of Indian States. (September 2019) - Roy, Subaran; Sen, Chitrakalpa; Sanyal, Rohini
The topic of growth convergence (or the lack of it) has always been one of the most important economic phenomena for Indian states. This study undertakes more than 3 decades of data for Indian states from the 1980s and traces convergence of state-level per capita income; breaking the data down into the subperiods based on time and levels of income using panel unit root tests. The results show no discernible evidence of convergence across the states, especially after post-liberalization. However, taking into account control variables for capital expenditure, development expenditure, and fiscal deficit, we find significant evidence for convergence of state-level per capita GDP. This indicates that the nature of inequality across states is not structural in nature and can be reduced through active policy interventions.